2020
DOI: 10.1093/nargab/lqaa095
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus infection induces widespread alterations of host cell splicing

Abstract: Influenza A viruses (IAVs) use diverse mechanisms to interfere with cellular gene expression. Although many RNA-seq studies have documented IAV-induced changes in host mRNA abundance, few were designed to allow an accurate quantification of changes in host mRNA splicing. Here, we show that IAV infection of human lung cells induces widespread alterations of cellular splicing, with an overall increase in exon inclusion and decrease in intron retention. Over half of the mRNAs that show differential splicing under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Differential splicing is observed in several disease conditions, leading to alternations of different transcript variants that can switch cell functionality, leading to disease development [37]. Several viruses have been demonstrated to interact with the host cellular splicing machinery that can help the viruses replicate efficiently by disrupting a number of host cellular processes to prevent innate antiviral responses [16][17][18][19][20]. Recent studies have shown that modulation of splicing is one of the key mechanisms for suppressing host response to [27,28,51,52].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differential splicing is observed in several disease conditions, leading to alternations of different transcript variants that can switch cell functionality, leading to disease development [37]. Several viruses have been demonstrated to interact with the host cellular splicing machinery that can help the viruses replicate efficiently by disrupting a number of host cellular processes to prevent innate antiviral responses [16][17][18][19][20]. Recent studies have shown that modulation of splicing is one of the key mechanisms for suppressing host response to [27,28,51,52].…”
Section: Discussionmentioning
confidence: 99%
“…All these different disease-specific transcripts can generate the different phenotypes, which impact the normal protein interaction networks, switch pathways and change the regulatory landscape of the cells that can drive the disease development [11][12][13][14][15]. Viral infections can also lead to widespread alternations of cellular splicing and altered transcripts, which are significantly associated with viral pathogenesis [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to angiosperms, we found that IR may not be the most prevalent type of AS in conifers. Taking all the above into account, together with the limited capacity of KisSplice to assemble long introns, which requires their full coverage by reads to be correctly assembled (Ashraf et al., 2020 ), and earlier described accelerated RNA Polymerase II kinetics and nuclear DNA hypomethylation during high temperature treatment (Jonkers & Lis, 2015 ; Lamelas et al., 2020 ), we propose that simultaneous availability of weak and strong splice sites due to loss of transcription control (Luco et al., 2011 ) could result in favored retention of introns flanked by weak splice sites. However, short introns are significantly more retained because their flanking splice sites are recognized as a unit (Monteuuis et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…We previously published a method called IRFinder, an algorithm for detecting and quantifying IR events, that is frequently used as a benchmark for IR detection and quantification [8][9][10][11][12]. This software and its associated database have been critical in the detection and interpretation of IR events in numerous studies [13][14][15][16][17][18][19]. However, building on 4 years of user feedback, it is apparent that IRFinder is lacking features that would enable bench scientists to more reliably identify actionable IR events, share IR data, and dynamically analyze changes in IR levels between multiple samples.…”
Section: Introductionmentioning
confidence: 99%